Noise Attenuation Characteristics of Exhaust Mufflers with Medium Size Farm Tractors - Selvan, M Muthamil; Mehta, C R (Journal of Agricultural Engineering, 2008)
Three mufflers viz., muffler A, muffler B and muffler C were evaluated for their noise reduction ability on two tractors of 23 kW pto power. The noise levels of the tractors were measured at operator's ear level at no load under laboratory condition, at no load on tar road during transport mode and during ploughing operation. The spectral analysis (one octave band) of noise levels was carried out in the frequency range from 31.5 to 16000 Hz. The noise levels increased at no load (under laboratory condition and at no load on tar road) at all the frequencies with the increase in engine speed. The highest noise level of the tractors at rated engine speed was observed at the frequency of 1 kHz with muffler A, muffler B, and existing muffler; and at 2 kHz with muffler C at no load under laboratory condition. The exhaust back-pressure increased with increase in engine speed at no load under laboratory condition for all the mufflers. The mounting of muffler B reduced noise levels by 4.1, 5.7 and 5.6 dB (A) on tractor-I and by 1.1, 1.4 and 4.0 dB(A) on tractor-II at 1000, 2000 and 4000 Hz frequencies, respectively as compared to the existing mufflers. It may be concluded that muffler B reduced noise levels considerably on both the tractors in conversational frequencies.